2022
DOI: 10.1089/tmj.2021.0642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on Patients in Adult Ambulatory Psychiatry: Using Patient-Rated Outcome Measures and Telemedicine

Abstract: Introduction: To examine the effects of coronavirus disease 2019 (COVID-19) on patients in an academic psychiatric ambulatory clinic, data from a measurement-based care (MBC) system were analyzed to evaluate impacts on psychiatric functioning in patients using telemedicine. Psychiatric functioning was evaluated for psychological distress (brief adjustment scale [BASE]-6), depression (patient health questionnaire [PHQ]-9), and anxiety (generalized anxiety disorder [GAD]-7), including initial alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…Thus, the specific conditions of telepsychiatric assessment and treatment did not impede the validity and reproducibility of diagnostic procedures in the study sample. This corroborates earlier findings that the implementation of patient reported outcome measures via telemedicine is a viable way of assessing psychiatric symptoms and psychosocial functioning as well as monitoring clinical changes in order to improve treatment outcomes ( 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the specific conditions of telepsychiatric assessment and treatment did not impede the validity and reproducibility of diagnostic procedures in the study sample. This corroborates earlier findings that the implementation of patient reported outcome measures via telemedicine is a viable way of assessing psychiatric symptoms and psychosocial functioning as well as monitoring clinical changes in order to improve treatment outcomes ( 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…As the data were solely collected during the COVID-19 pandemic for nonclinical samples while the clinical sample’s data were collected before and during the pandemic, there is a possibility that the pandemic affected and increased overall mental health distress in these populations, in line with the growing research of pandemic’s negative influence on mental health (Horigian et al, 2021; Islam et al, 2021; Pierce et al, 2020; Serafini et al, 2020). Furthermore, another study that utilized the BASE-6 for adult psychiatric outpatients showed total scores between 22.71 and 26.38 during the COVID-19, which is higher than the total score of the clinical population in this study (Kablinger et al, 2022). These results imply the impact of the pandemic on clinical populations and suggest that the current study’s clinical sample’s scores could have been even higher if the data were solely collected during the pandemic, rather than before and throughout COVID-19.…”
Section: Discussioncontrasting
confidence: 74%
“…The current study used the Brief Adjustment Scale-6 ( Cruz et al, 2020 ) to assess respondents’ psychological adjustment (e.g., “To what extent have you felt irritable, angry, and/or resentful this week?”). The Brief Adjustment Scale-6 was previously tested for its validity in the context of COVID-19 ( Kablinger et al, 2022 ). All six items on the scale are scored based on a 5-point scale ranging from 1 (not at all) to 5 (extremely).…”
Section: Methodsmentioning
confidence: 99%